From physical to financial contagion: the COVID-19 pandemic and increasing systemic risk among banks - Eduard Baumöhl; Elie Bouri; Thi-Hong-Van Hoang; Syed Jawad Hussain Shahzad; Tomáš Výrost (ZBW – Leibniz Information Centre for Economics, 2020)
Over the last few decades, large banks worldwide have become more interconnected, and as a result, the failure of one can trigger the failure of many. In finance, this phenomenon is often known as financial contagion, which can occur as a domino effect. In this paper, we show an unprecedented increase in bank interconnectedness during the outburst of the COVID-19 pandemic. We measure how extreme negative stock market returns for one bank spill over to all other banks within the network, and on this basis, we propose a new measure of systemic risk among banks. Our results indicate that the systemic risk and the density of the spillover network have never been as high as they have been during the pandemic, not even during the 2008 global financial crisis. Policy makers and regulatory authorities should be particularly cautious regarding this interconnected financial environment, as second waves of the pandemic could pose a significant danger to the worldwide economy, and the “it's-just-a-flu” narrative will no longer be an option.
Keywords: G01; G15; G21; G28; C21; 330; systemic risk; banks; COVID-19; pandemic; cross-quantilogram; financial networks; interconnectedness